The great wolf rescue : saving the red wolves - Markle, Sandra (Sandra Markle's science discoveries, 2024)
"Red wolves had been hunted until only fourteen survived in the wild. So scientists hatched a daring plan--capture all of the wild red wolves and breed them in captivity. Discover the story of their recovery"--